Madeira’s ptyctimous mites (Acari, Oribatida) - Niedbała, Wojciech; Dabert, Miroslawa (Zootaxa, 2013)
In the material recently collected in Madeira, 16 species of ptyctimous mites have been found. A new species of Austrophthiracarus rabacalensis Niedbała sp. nov. has been described. The presence of P. globosus and S. (R.) ortizi, reported earlier from Madeira has not been confirmed, but P. anonymus and P. montanus, so far not reported from this island, have been found. All 16 species identified in the material from Madeira studied occur in the Palaearctic Region; four of them are endemites, seven occur in western Palaearctic, four are panpalaearctic, while one is a semicosmopolitan. Morphological analysis has revealed a high similarity of two endemic species of Madeira with two European species: Ste-ganacarus (Steganacarus) crassisetosus is similar to Steganacarus (Steganacarus) applicatus, while Steganacarus (Ste-ganacarus) similis to Steganacarus (Steganacarus) spinosus. DNA-barcode analysis using COI and D2 28S rDNA sequences confirmed the species status of these four species. The phylogenetic analyses of COI amino acid data and D2 28S rDNA sequences suggest a closer relationship between S. (S.) crassisetosus and S. (S.) applicatus, pointing to a great genetic distance between S. (S.) spinosus and the other species of Steganacarus (Steganacarus).